A PROPOSED FRAMEWORK TO APPLY OPERATIONAL EXCELLENCE (OPEX) AS A BUSINESS STRATEGY - Cahyo, Winda Nur (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2019)
This study is initiated from a perspective that OPEX is not one of the mainstream issues in the area of productivity improvement. However, the potency of OPEX applied to assist the management to improve the productivity is solid. From the literature review, it is found that this circumstance is probably caused by the confusions of the researcher and management about OPEX. In this paper, OPEX is then considered as a business strategy in order to narrow the discussion and reduce the confusion. As a business strategy, it is important to develop a framework to apply it in every level of organisation. Because, framework of OPEX has not yet found, a framework is proposed in this research based on the structure of OPEX. The framework is then applied in two case studies at two different company. The result shows that the framework is capable to assist the management to achieve the goal of OPEX.